Ultrasound-guided paravertebral blockade reduced perioperative opioids requirement in pancreatic resection: A randomized controlled trial - Han, Ye; Dai, Yuanqiang; Shi, Yaping; Zhang, Xiaoxiu; Xia, Boyang; Ji, Qiufang; Yu, Xiya; Bian, Jinjun; Xu, Tao (Frontiers in Surgery, 2022)
Background: Perioperative opioid usage for pain control has been found to be associated with side effects and adverse prognosis. In this study, we hypothesized that paravertebral block could reduce the consumption of opioids in pancreatic resection surgery. Methods: We conducted a prospective, randomized trial. Patients with resectable pancreatic cancer were allocated into either bilateral paravertebral block combined with general anesthesia (PTB group) or only general anesthesia (Control group). Primary endpoint was the perioperative consumption of opioids (sufentanil and remifentanil). Main secondary endpoints included pain scores, complications and serum cytokine levels. Results: 153 patients were enrolled, and 119 cases were analyzed. Compared to control group, patients in PTB patients were with significantly lower perioperative (30.81 and 56.17 ug), and intraoperative (9.58 vs 33.67 ug) doses of sufentanil (both p<0.001). Numerical rating scale (NRS) scores of pain were comparable between the two groups. No statistical differences in complications were detected. Conclusion: Bilateral paravertebral block in combination with general anesthesia reduced the perioperative consumption of opioids by 45%. Registration number: ChiCTR1800020291 (available on http://www.chictr.org.cn/).